Knowledge, Attitude and Practice regarding Prevention and Control of COVID-19 among Nurses of Tertiary Care Hospital - Paudel, Radha; Shrestha, Sarita; Gurung, Laxmi (Journal of College of Medical Sciences-Nepal, 2021)
Background: COVID-19 has become a global health threat and the disease burden is expected to increase more. Nurses are the front lines of COVID management. Because this work requires close personal exposure to patients with COVID-19, nurses are at high risk of infection, contributing to further spread. Nurses’ knowledge, attitudes, and practices can influence the prevention and control of pandemic. Thus, the aim of the study was to assess knowledge, attitude, and practice regarding the prevention and control of COVID-19 among nurses. Methods: Descriptive cross-sectional study design was carried out among 141 nurses from the central hospital, Kathmandu. A purposive sampling technique was used and the data collection date was June 5 to July 20, 2020. A self-administered semi-structured questionnaire was used. The data were analyzed using descriptive statistics. Results: The study showed that 60.3% of the participants had good knowledge, 53.2% of them had acceptable practice and a cent percent (100%) of them had a positive attitude on the preventive and control measures against COVID-19. More than 3/4th (75.8%) of them were agreed to handle the COVID-19 outbreak confidently in their healthcare setup. Although, 85.8% of participants were worried that they and their family members will probably get infected with COVID-19 while working in the hospital. However, 39% of them were feeling isolated by their community, and relatives due to their profession. Conclusions: Nurses have good knowledge, a positive attitude, and acceptable practice about prevention and control of COVID-19. However, the level of some knowledge and practice was still lower than that expected. Keywords: Attitude; COVID; Knowledge; nurses; prevention and control; practice